Ways and Possibilities of Preparing Data in Airport for Balance in Check-In and Check-Out... - Radoš, Jerko; Miše, Mihaela; Suić, Ivan (Promet - Traffic&Transportation, 2012)
This paper deals wilh the criteria and requirements in developinggeneral autonomous software related to handling aircraftat the ailp011. ft gives an ove1view of almost all the influencingfactors which are relevant to ’processing’ an aircraftboth upon aiTival as well as on departure. It gives a brief descriptionof the conventional balancing method which is beingused, of 1/ze latest advancement in the field, and it offers a concretesuggestion for improving the reliability of criteria andresultsin aircraft handling.The main idea of this initial work is to unify all the necessaryactivities and to register them. by one computer, from landinguntil take-off, including computer communica1ion withother ai1ports and companies. Cun·ently, the programs of certainair companies are being used and they have produced individualsoftware in co-operation wilh the manufacturers only forcertain types of aircraft that are cwTently employed by !hem.Since the range of aircraft types landing at ahports is growing,!here is the need to find a universal program which can calculatethe balance chart for each aircraft based, of course, onthe manufacturer-supplied design data.